The extent to which Latina/o preservice teachers demonstrate culturally responsive teaching practices during science and mathematics instruction - Hernandez, Cecilia M. (Kansas State University, 2011)
Complex social, racial, economic, and political issues involved in the practice of teaching today require beginning teachers to be informed, skilled, and culturally responsive when entering the classroom. Teacher educators must educate future teachers in ways that will help them teach all children regardless of language, cultural background, or prior knowledge. The purpose of this study was to explore the extent to which culturally and linguistically diverse (CLD) novice teachers described and demonstrated culturally responsive teaching strategies using their students’ cultural and academic profiles to inform practice in science and mathematics instruction. This qualitative exploratory case study considered the culturally responsive teaching practices of 12, non-traditional, Latina/o students as they progressed through a distance-based collaborative teacher education program. Qualitative techniques used throughout this exploratory case study investigated cultural responsiveness of these student teachers as they demonstrated their abilities to: a) integrate content and construct knowledge; b) illustrate social justice and prejudice reduction; and c) develop students academically during science and mathematics instruction. In conclusion, student teachers participating in this study demonstrated their ability to integrate content by: (1) including content from other cultures, (2) building positive teacher-student relationships, and (3) holding high expectations for all students. They also demonstrated their ability to facilitate knowledge construction by building on what students knew. Since there is not sufficient data to support the student teachers’ abilities to assist students in learning to be critical, independent thinkers who are open to other ways of knowing, no conclusions regarding this subtheme could be drawn. Student teachers in this study illustrated prejudice reduction by: (1) using native language support to assist students in learning and understanding science and math content, (2) fostering positive student-student interactions, and (3) creating a safe learning environment. Results also indicated that these student teachers demonstrated their ability to develop students academically by creating opportunities for learning in the classroom through their knowledge of students and by the use of research-based instructional strategies. However, based on the data collected as part of this study, the student teachers’ abilities to illustrate or model social justice during science and math instruction were not demonstrated.
Keywords: Preservice teachers; Latina; Science; Math; Culturally Responsive Teaching; Elementary instruction; Education, General (0515); Elementary Education (0524); Science Education (0714)